Multifunctional PVDF membranes incorporating graphene, TiO 2, and nanocellulose: synergistic effects on filtration and antifouling performance - Anthonette, James; Rezaur, Rahman; Khairul Anwar, Mohamad Said; Murtala, Namakka; M., Shahabuddin; Muneera S. M., Al-Saleem; Jehan Y., Al-Humaidi; Mohammed M., Rahman; Mohammed Abdus, Salam (Royal Society of Chemistry, 2025)
Methylene blue (MB) remains one of the most resilient contaminants in industrial wastewater which presents serious threats to both environmental integrity and human health. Its high chemical stability and resistance to natural degradation render most conventional treatment methods ineffective. As such, this study aimed to develop a multifunctional nanocomposite membrane that mitigates membrane fouling, enhances dye separation, and improves water permeability. Correspondingly, a modified phase inversion method was employed to fabricate polyvinylidene fluoride (PVDF) membranes reinforced with bamboo-derived nanocellulose (NC), titanium dioxide (TiO2), and varying graphene (GR) contents (0–1 wt%). Characterization through FTIR confirmed the successful integration of GR through the attenuation of semi-ionic C–F bonds and the emergence of CC stretching bands while XRD results revealed that a